LEAPing on with language: An on-line language programme to support classroom teachers and parents of primary school children (aged 5–11 years). (May 2014) - Clare Allen, M; Kendrick, Andrew; Archbold, Sue; Harrigan, Suzanne
<x content-type="archive" xml:space="preserve">Abstract</x> The Leaping on with Language programme provides a combination of strategies and activities to accelerate children's spoken language use from simple sentences to complex language. Using a conversational philosophy it expands the building blocks of language (vocabulary, grammar, speech), whilst emphasising the importance of developing independent social communication and acknowledging a child's developing self esteem and self identity between the ages of 4–11. Three pilot projects evaluated the programme with a total of 51 delegates. The outcomes were hugely positive. Changes in behaviour were reported from the 3rd pilot 1 month later. Comments regarding the length of training, practical strategies and more film clips were implemented. Leaping on with language is now a free to access resource available on line.